Marker-assisted selection of bacterial blight broad spectrum resistance genes Xa33 and Xa38 into CO43 in ICF3 generation - R. Vennisa; N. Kumaravadivel and; A. Ramanathan (Electronic Journal of Plant Breeding, 2018)
Bacterial Leaf Blight (BB) is one of the devastating diseases in Southern India. An elite rice variety, CO43 which is a medium duration variety (135 days) with average yield (6.3t/ha) and does not show resistance to Bacterial Leaf Blight (BB). Scientists had discovered several BB resistant genes which are both dominant and recessive and is denoted as Xa and xa respectively. The current study is on the two genes Xa33 and Xa38 which are pyramided and is located on chromosome number 7 and 4 respectively. The rice genotypes FBR1-15 and PR114 were used as donors of Xa33, Xa38. The markers RMWR7.5 linked to Xa33 and Os04g53050-1 specific to Xa38 were validated in parents (CO43/ FBR1-15 and CO43/ PR114) and ICF3 populations to carry out Marker Assisted Selection (MAS). The segregating population of ICF3 were genotyped and the homozygous plants were subjected to artificial screening. The plants which showed resistance compared to CO43 are potential source of disease resistance which could be evaluated further and can be utilized for further breeding program.